Cross-cutting themes in didactic productions by members of the Programa de Residência Pedagógica at FCL Unesp/Assis (Revista Brasileira Multidisciplinar, 2025)
During the 2020-2022 cycle of the Programa de Residência Pedagógica, a research study titled "Initial Training of Spanish Language Teachers in the Programa de Residência Pedagógica of FCL Unesp/Assis: Constructing Critical Teaching" (ÁVILA, 2022) was developed at the master's level, stemming from a training workshop offered to residents of the Letters course - Spanish language subproject of FCL Unesp/Assis. Throughout the preparation and execution of the workshop, during which action research was conducted, the topic of "cross-cutting themes" was not formally named as a subject of knowledge in the activity schedule. Subsequently, enrolling in the specialization course in Cross-Cutting Themes at IFSP Salto provided an understanding that the construction of critical teaching, by presenting and problematizing historical, cultural, political, and geographical contexts involved in language teaching, needs to implicitly address social issues. With the aim of reflecting on the importance of cross-cutting themes in the teaching of Spanish as a foreign language, we revisited the completed research, specifically focusing on the four didactic sequences produced by the residents at the conclusion of the workshop. We conducted a qualitative documentary analysis to verify the presence of cross-cutting themes in the productions and, if present, how the approach was or could be conceived. Without receiving this designation, cross-cutting themes were identified both as a reality and a possibility in the didactic proposals, demonstrating that resident graduates understood the significance of connecting language with the social world when teaching Spanish as a foreign language.
Keywords: Cross-Cutting Themes; Initial Teacher Training; Spanish Language Teaching; Residência Pedagógica.